2014
DOI: 10.1021/bc500074a
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Decationized Polyplexes for Cell Specific Gene Delivery

Abstract: Decationized polyplexes have previously shown unique features, especially regarding their excellent cytocompatibility and very low degree of nonspecific cellular uptake. In the present study, targeted disulfide cross-linked decationized polyplexes were composed of a core of disulfide cross-linked poly(hydroxypropyl methacrylamide) (pHPMA) stably entrapping plasmid DNA (pDNA) and a shell of poly(ethylene glycol) (PEG) decorated with folate molecules. Folate was used as targeting ligand because of its high bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 50 publications
5
43
0
Order By: Relevance
“…This result is consistent with the previous report showing a similar decrease of transfection efficiency for PEG-FA conjugated vector in A549 cells. 47 In addition, the fluorescence images ( Figure S6, Supporting Information) confirmed these results. In conclusion, the divalent FA coupling to PME through PEG spacer was more effective in improving transfection activity than the monovalent FA coupling.…”
Section: ■ Results and Discussionsupporting
confidence: 61%
“…This result is consistent with the previous report showing a similar decrease of transfection efficiency for PEG-FA conjugated vector in A549 cells. 47 In addition, the fluorescence images ( Figure S6, Supporting Information) confirmed these results. In conclusion, the divalent FA coupling to PME through PEG spacer was more effective in improving transfection activity than the monovalent FA coupling.…”
Section: ■ Results and Discussionsupporting
confidence: 61%
“…Additionally, as anticipated, decationized polyplexes have shown an excellent safety profile and extensive in vitro tests have shown that decationized polyplexes do not interfere with cell viability nor induce membrane destabilization at any of the doses tested [19,20]. Furthermore, the neutral block copolymer pHP--PEG that forms decationized polyplexes showed excellent cytocompatibility upon incubation with HUVEC cells.…”
Section: Decationized Polyplexes Propertiesmentioning
confidence: 56%
“…On the other hand, for the cell line (A549) with low folate receptor expression, a similar uptake was observed for both targeted and nontargeted decationized polyplexes. Furthermore, the improved cellular uptake for targeted systems had a direct correlation with improved transfection observed in OVCAR-3 cells [20]. Importantly, the nontargeted cationic system showed the highest cellular uptake, mainly due to nonspecific interaction between the positively charged polyplexes membrane anionic components, which is not favorable for highly specific targeted delivery which requires low uptake by nontarget cells (Figure 2A).…”
Section: Decationized Polyplexes Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding the optimization of cell selectivity, multifunctional nanocarriers comprising pDNA-compacting amino acids and targeting moieties have been developed for delivery of genetic material to folate receptor overexpressed in HeLa cervix cancer cells [58]. Recently, to address these issues correlated with the cationic net-charge of polyplexes and stimuli-responsive DNA release in in vivo applications, Novo et al has developed an elegant approach in which polyplexes were initially formed by electrostatic interaction between polymer-pDNA followed by stabilization of the particle through disulfide linkages and finally decationization by removal of the polymer cationic moieties [62]. The final nanocarriers presented negative surface, redox-responsive behavior and selectivity towards folate-receptor-positive cancer cells [62].…”
Section: Therapeutic Applications Of Mcdna Biopharmaceuticalsmentioning
confidence: 99%